CRISPR/Cas9/sgRNA-mediated targeted gene modification confirms the cause-effect relationship between gyrA mutation and quinolone resistance in Escherichia coli. Issue 13 (14th May 2018) - Qiu, Haixiang; Gong, Jiansen; Butaye, Patrick; Lu, Guangwu; Huang, Ke; Zhu, Guoqiang; Zhang, Jilei; Hathcock, Terri; Cheng, Darong; Wang, Chengming
Abstract: Quinolones are broad-spectrum antibiotics that have been used for decades in treating bacterial infections in humans and animals, and subsequently bacterial resistance to these agents has increased. While studies indicated the relationship between gyrA mutations and bacterial resistance to quinolones, CRISPR/Cas9 was used in this study to investigate causal role of gyrA mutation in the quinolone resistance. In this study, 818 clinical Escherichia coli isolates were analyzed for gyrA mutations and their resistance to quinolones. The CRISPR/Cas9 system was used to generate gyrA mutations in quinolone-susceptible E. coli ATCC 25922, and quinolone-resistant clinical E. coli . The antimicrobial resistance prevalence rate in E. coli against nalidixic acid, ciprofloxacin and enrofloxacin was 77.1% (631/818), 51.1% (418/818) and 49.8% (407/818), respectively. The gyrA mutations were identified in nucleotide positions 248, 255, 259, 260, 261, 273 and 300, and mutations at positions 248 and 259 resulting in amino acid changes at positions 83 and 87 were associated with quinolone resistance. Double-site amino acid mutations increase resistance to quinolones. The gyrA mutations causing changes at amino acids 83 and 87 reversed the features of quinolone resistance in ATCC and clinical strains, verifying the causal role of gyrA mutation in the quinolone resistance of E. coli . Abstract : CRISPR/Cas9/sgRNA was used to verify the causal role of gyrA mutation in the quinolone resistance of E. coli .